BENTUK PERALIHAN HAK ATAS TANAH YANG DAPAT DILAKUKAN OLEH WARGA NEGARA ASING AKIBAT PERCAMPURAN HARTA DALAM PERKAWINAN - Larashati, Ida Ayu Putu; Dirksen, Anak Agung Ngurah Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013)
Obtaining property rights over land to foreign nationals because of commingling marital property as referred to in Article 21 paragraph (3) Law - Law of the Republic of Indonesia on Basic Regulation - Agrarian Law (BAL) it is necessary to transfer land rights should be done by the citizens the stranger. Transitional forms of land rights that can be done by foreign nationals due to commingling marital property is through the transfer of property rights to land through purchase, transfer ownership of the land through a grant and release of title to land use rights along with the application. This paper uses this type of research or study normative legal bibliography.
Keywords: Transition, Foreign Nationals, Mixed Marriage, Intermarriage